Tourism marketing in Sabah: A study on Kinabalu Park as a leisure and holiday destination for domestic tourist market / Gua Hui B Manak - Manak, Gua Hui (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2002)
Tourism is not only arguably the world's largest industry, it also involves the greatest flows of people on the surface of the earth. It is a major agent of change and as one of the most visible expressions of globalization. Tourists and tourism development affect almost every country. They produce impacts upon communities, environments and economies. At the same time, tourism is a source of immerse enjoyment and pleasure for hundreds of millions of people and creates contact and communication between peoples from different regions and cultures. This study discusses the marketing of Kinabalu Park as a domestic tourist destination for leisure and holiday, analyzes the motivational factors underlying decisions to visit Kinabalu Park by the various existing local market segments. The tourism industry is crucial to Sabah as the state government sees tourism as an avenue to diversify the state's economy. However, the review on the local tourist industry and its literature through the marketing plans and l domestic tourism reports for the last five years between 1995 to 1999 shows that the domestic tourist arrival to the state has not been performing very well. One of the main factors leading to this trend was the lack of awareness from domestic market towards the various tourist destinations in Sabah particularly Kinabalu Park.